Matched unrelated donor allogeneic transplantation provides comparable long-term outcome to HLA-identical sibling transplantation in relapsed diffuse large B-cell lymphoma - Avivi, Irit; Canals, C.; Vernant, J.-P.; Wulf, G.; Nagler, A.; Hermine, O.; Petersen, E.; Yakoub-Agha, I.; Craddock, C.; Schattenberg, A.; Niederwieser, D.; Thomson, K.; et al. (Bone marrow transplantation, 2014)
The objective of this retrospective analysis was to compare outcomes of patients with diffuse large B-cell lymphoma (DLBCL) who received either a matched sibling (sib) or an unrelated donor (URD) allogeneic hematopoietic cell transplantation (allo-HCT). Long-term outcome of 172 DLBCL patients receiving URD-HCT between 2000 and 2007 and reported to the European Group for Blood and Marrow Transplantation, was compared with that of 301 subjects, allografted from sib-HCT. With a median follow-up of 45 months, 3-year PFS approached 35% for both groups; overall survival (OS) was 42% for sib-HCT versus 37% for URD (NS). Multivariate analyses confirmed that donor type was not associated with differences in non-relapse mortality (NRM), relapse rate (RR), PFS or OS. Poor performance status (PS) and refractory disease adversely affected PFS and OS. Prior auto-SCT and multiple previous therapies predicted for shorter PFS. NRM was adversely affected by older age (⩾50 years), poor PS and refractory disease, and RR by time from diagnosis to allo-HCT of <36 months, prior auto-SCT, refractory disease, poor PS and in vivo T-cell depletion with alemtuzumab. This large study shows for the first time that URD-HCT is not inferior to sib-HCT, providing a reasonable therapeutic approach for DLBCL patients, having no HLA-identical sibling available.
Gesehen am 03.09.2020